El diseño técnico pedagógico: Aspectos conceptuales y metodológicos - Rodríguez de los Ríos, Luis Alberto (2022)
An analysis of the theoretical-conceptual and methodological bases of the techno-pedagogical design is presented, considering its omnipresence in the context of the non-face-to-face, remote and virtual educational modality in conditions of the pandemic caused by COVID-19, in exceptional conditions and sustainability perspectives. The authors are convinced of the fecundity and urgent applicability of techno-pedagogical design in the current educational scenario signed by virtuality with the transformative support of available digital tools. In this article, we mention some theories that can be referenced to make decisions about the process pedagogy and learning. As well as some applications reported in recent years.